2018
DOI: 10.1111/liv.13972
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic fat as clinical outcome and therapeutic target for nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is rapidly becoming the leading cause of advanced liver disease in Western countries. NAFLD is defined in the presence of increased hepatic fat content, which is mainly stored under the form of neutral lipids within intracellular droplets and is not explained by at risk alcohol intake. In order to understand the pathogenesis, monitor the progression and find novel treatments for this condition, previous research efforts mainly addressed the role of inflammation. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…Non‐alcoholic fatty liver disease (NAFLD), defined as accumulation of excess fat in the liver, is increasing in prevalence worldwide in association with rising obesity rates to become the most common cause of chronic liver disease in the world, afflicting 25% of the global population . Hepatic lipid accumulation is a key driver of NAFLD progression to non‐alcoholic steatohepatitis (NASH), cirrhosis and hepatocellular carcinoma through inflammation and fibrosis and represents a major therapeutic target for NAFLD . Structured weight‐loss programmes which include frequent contact with healthcare providers are recommended but can be difficult to sustain because of inadequate time and effort and metabolic adaptations which oppose weight loss .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Non‐alcoholic fatty liver disease (NAFLD), defined as accumulation of excess fat in the liver, is increasing in prevalence worldwide in association with rising obesity rates to become the most common cause of chronic liver disease in the world, afflicting 25% of the global population . Hepatic lipid accumulation is a key driver of NAFLD progression to non‐alcoholic steatohepatitis (NASH), cirrhosis and hepatocellular carcinoma through inflammation and fibrosis and represents a major therapeutic target for NAFLD . Structured weight‐loss programmes which include frequent contact with healthcare providers are recommended but can be difficult to sustain because of inadequate time and effort and metabolic adaptations which oppose weight loss .…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic lipid accumulation is a key driver of NAFLD progression to non‐alcoholic steatohepatitis (NASH), cirrhosis and hepatocellular carcinoma through inflammation and fibrosis and represents a major therapeutic target for NAFLD . Structured weight‐loss programmes which include frequent contact with healthcare providers are recommended but can be difficult to sustain because of inadequate time and effort and metabolic adaptations which oppose weight loss . A meta‐analysis of 80 controlled weight‐loss intervention studies found a mean attrition rate of 31%, while less than 40% of attendees adhered to unsupervised diet and exercise programmes for 3‐12 months …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In brief, the role of HSD17B13 in human physiology and the molecular mechanism behind the genetic protection are far from being clear. The interplay between HSD17B13 and PNPLA3 is a further complicating issue, especially given that PNPLA3 itself is a potential target for therapeutic inhibition in the context of FLD . It will be important to determine what proportion of the protective effect of the HSD17B13 variant is mediated by PNPLA3 downregulation.…”
mentioning
confidence: 99%